Find all triplets $(x,y,p)$ such that $\frac{xy^3}{x+y}=p$, where $x$ and $y$ are positive integers and $p$ is prime. I don't have much experience with Diophantine equations such as this, and I don't know how to fully solve it. After a bit of fiddling around I found that $(n^4-n,n,n^3-1)$ is a solution if $n^3-1$ is prime, so $(14,2,7)$ is one solution. I suspect this is the only solution since $n^3-1$ is not prime for $n>2$, and I don't see any other obvious ways to generate solutions.

  • $\begingroup$ $n^3-1=(n-1)(n^2+n+1)$ $\endgroup$ – paf Aug 20 '16 at 23:33
  • $\begingroup$ Yes I see that, but I'm wondering if there are other solutions, and if not how to show that? $\endgroup$ – zagaluke Aug 20 '16 at 23:36
  • $\begingroup$ $x(y^3-p)=yp\implies x$ and $y^3-p$ divides $yp$. $\endgroup$ – Simply Beautiful Art Aug 20 '16 at 23:40
  • $\begingroup$ This is (obviuosly) not an answer, but this problem looks like a family of very difficult problems (if you don't know the trick) that can be solved using infinite descent. $\endgroup$ – ajotatxe Aug 20 '16 at 23:56

We have: $y = \dfrac{xy^3}{p} - x$. Thus $p \mid xy^3$. So either $p \mid x$ or $p \mid y^3$ , hene $p \mid y$ since it is a prime number. If $p \mid x \implies x = kp\implies y = ky^3 - kp\implies kp = ky^3-y = y(ky^2-1)$. thus $p \mid y$ or $p \mid ky^2-1$. We have again two cases: if $p \mid y$, then $y = np \implies kp = np(ky^2-1)\implies k = n(ky^2-1)\implies n = \dfrac{k}{ky^2-1}\le \dfrac{k}{k-1}< 2\implies n = 1\implies k = ky^2-1\implies k = \dfrac{1}{y^2-1}\notin \mathbb{N}$. Thus $p \nmid y$, and we must have $p \mid ky^2-1\implies ky^2-1 = pm\implies kp = y(pm)\implies k = my\implies my^3 - 1 = pm\implies m(y^3-p) = 1\implies m = 1 = y^3-p\implies p = y^3-1 = (y-1)(y^2+y+1)\implies y - 1 = p, y^2+y+1 = 1\implies y = 0$ which is absurd, so $y-1 = 1, y^2+y+1 = p\implies p = 2^2+2+1 = 7, k = my = 1(2) = 2, x = kp = 2(7) = 14$. Thus $(x,y,p) = (14,2,7)$. The second case is $p \mid y$, thus $y = rp\implies rp = \dfrac{xr^3p^3}{p} - x\implies rp = xr^3p^2-x\implies x = (xr^3p-r)p\implies p \mid x \implies x = tp\implies r = tr^3p^2 -t=t(r^3p^2-1)\implies t \mid r$. Also, $t = r(tr^2p^2-1)\implies r \mid t\implies r = t\implies 1 = t^3p^2-1\implies 2 = t^3p^2$, and this equation has no solution in $\mathbb{N}$. Thus the only solution to the given equation is: $(x,y,p) = (14,2,7)$.

  • $\begingroup$ nice and quick calculus :) $\endgroup$ – user354674 Aug 21 '16 at 1:29
  • $\begingroup$ Thank you for the answer! This suggests a systematic way to solve similar problems so I appreciate it $\endgroup$ – zagaluke Aug 21 '16 at 1:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.